Reducing phenotypic instabilities of a microbial population during continuous cultivation based on cell switching dynamics. Issue 10 (19th June 2021) - Nguyen, Thai M.; Telek, Samuel; Zicler, Andrew; Martinez, Juan A.; Zacchetti, Boris; Kopp, Julian; Slouka, Christoph; Herwig, Christoph; Grünberger, Alexander; Delvigne, Frank
Abstract: Predicting the fate of individual cells among a microbial population (i.e., growth and gene expression) remains a challenge, especially when this population is exposed to very dynamic environmental conditions, such as those encountered during continuous cultivation. Indeed, the dynamic nature of a continuous cultivation process implies the potential diversification of the microbial population resulting in genotypic and phenotypic heterogeneity. The present work focused on the induction of the arabinose operon in Escherichia coli as a model system to study this diversification process in continuous cultivations. As a preliminary step, the green fluorescent protein (GFP) level triggered by an arabinose‐inducible ParaBAD promoter was tracked by flow cytometry in chemostat cultivations with glucose‐arabinose co‐feeding. For a wide range of glucose‐arabinose co‐feeding concentrations in the chemostats, the simultaneous occurrence of GFP positive and negative subpopulation was observed. In the second set of experiments, continuous cultivation was performed by adding glucose continuously and arabinose based on the capability of individual cells to switch from low GFP to high GFP expression states, performed with a technology setup called segregostat. In the segregostat cultivation mode, on‐line flow cytometry analysis was used for adjusting the arabinose/glucose transitions based on the phenotypic switching profiles of the microbial population. This strategy allowed finding an appropriate arabinose pulsing frequency, leading to prolonged maintenance of the induction level with a limited increase in the phenotypic diversity for more than 60 generations. The results suggest that the steady forcing of individual cells into a given phenotypic trajectory may not be the best strategy for controlling cell populations. Instead, allowing individual cells to switch periodically around a predefined threshold seems to be a more robust strategy leading to oscillations, but within a predictable cell population behavior range. Abstract : Uncontrolled phenotypic diversification leads to destabilized continuous culture. Promoting phenotypic switch based on the alternance between environmental conditions leads to and oscillating but homogeneous population of cells.